Laws of neurofeedback influence on condition of highly skilled gymnasts-women - Strizhkova, T.; Cheprapkina, L.; Strizhkova, O. (Journal of Human Sport & Exercise, 2012)
Carried out research showed that changes of complex-coordinated activity, self-estimation of functional condition and cardiointervalographic indexes of the highly skilled gymnasts-women after neurofeedback course depended on dynamics of cerebrum theta-, alpha-rhythm during the neurofeedback sessions and successfulness of the alpha-rhythm increasing technical skill mastery generally. The neurofeedback which was begun in follicular phase of ovarian-menstrual cycle (OMC) led to the most pronounced positive changes of functional condition self-estimation. This method conducted complex-coordinated activity improvement and vegetative parameters stabilization of sportswomen in ovulatory phase. The least neurofeedback efficiency was in luteal phase.